Analysis of spatio-temporal changes and driving forces of cultivated land in China from 1996 to 2019 - Li, Jianfeng; Han, Jichang; Zhang, Yang; Sun, Yingying; Peng, Biao; Xie, Xiao; Guo, Chao; Ye, Huping (Frontiers in Environmental Science, 2022)
Cultivated land is an important prerequisite and guarantee for food production and security, and the change of cultivated land resources in China has always been concerned. National land survey is an effective way to accurately grasp the area and distribution of cultivated land resources. However, due to the differences in technical means at different stages, there are obvious breakpoints among the cultivated land area data of the three land surveys in China, which hinders the in-depth study of the spatio-temporal distribution of cultivated land in long-time series. The ARIMA model is used to reconstruct the cultivated land area data from 1996 to 2019 based on the data of the third land survey in China. The spatio-temporal variation characteristics of cultivated land area are explored by using GIS spatial analysis, and the driving factors of cultivated land change are analyzed based on GeoDetector from the perspective of social, economic, agricultural and natural. The results show that the area of cultivated land in China decreased continuously from 1996 to 2019. From 1996 to 2019, there were obvious spatial differences in the change of cultivated land area in 31 provincial units. From 1996 to 2008, the cultivated land area in 29 provinces showed a downward trend, especially in the central and northern regions. From 2008 to 2019, the cultivated land area in the underdeveloped areas increased significantly, while the rest showed a downward trend. Factor detection found that the q values of population, disaster area, regional GDP, grain output and the proportion of the added value of the primary industry were all more than 0.5, which had an important impact on the change of cultivated land area. The explanatory power of the interaction between factors on the change of cultivated land area is enhanced in different degrees compared with the single factor effect, which is manifested in the enhancement of bilinear or nonlinear enhancement, and the interaction of different factors promotes the change of cultivated land area. The change of cultivated land area is the result of complex interaction between factors, and is closely related to the land policy in the same period.